End of the line: the spatial framing of high-speed rail in Wisconsin - Culver, Gregg (Journal of transport geography, 2016)
This paper aims to contribute toward filling a gap in the literature on the recent high-speed rail (HSR) initiative in the United States by offering a case study on the politics of Wisconsin HSR, one of three states to reject its federal HSR funding in dramatic fashion in late 2010 and early 2011. Based on a qualitative content analysis of statewide news media, complemented by stakeholder interviews, participant observation, and mobile methods, I find that the predominant spatial frame of the project (or how people envisioned the spatialities of the project to be) shifted throughout the controversy, and in such a way that undermined the overall logic of the project. Aside from its implications for literature on HSR in the transport geography literature, this research contributes the concept of spatial framing to politics of mobility research.